Bone Regeneration in Load-Bearing Segmental Defects, Guided by Biomorphic, Hierarchically Structured Apatitic Scaffold - Kon, Elizaveta; Salamanna, Francesca; Filardo, Giuseppe; Di Matteo, Berardo; Shabshin, Nogah; Shani, Jonathan; Fini, Milena; Perdisa, Francesco; Parrilli, Annapaola; Sprio, Simone; Ruffini, Andrea; Marcacci, Maurilio; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
The regeneration of load-bearing segmental bone defects remains a significant clinical problem in orthopedics, mainly due to the lack of scaffolds with composition and 3D porous structure effective in guiding and sustaining new bone formation and vascularization in large bone defects. In the present study biomorphic calcium phosphate bone scaffolds (GreenBoneTM) featuring osteon-mimicking, hierarchically-organized, 3D porous structure and lamellar nano-architecture were implanted in critical cortical defect in sheep and compared with allograft. Two different types of scaffolds were tested: one made of ion-doped hydroxyapatite/β-tricalcium-phosphate (GB-1) and one made of undoped hydroxyapatite only (GB-2). X-ray diffraction patterns of GB-1 and GB-2 confirmed that both scaffolds were made of hydroxyapatite, with minor amount of β-TCP in GB-1. The chemical composition analysis, obtained by ICP-OES spectrometer, highlighted the carbonation extent and the presence of small amounts of Mg and Sr as doping ions in GB-1. SEM micrographs showed the channel-like wide open porosity of the biomorphic scaffolds and the typical architecture of internal channel walls, characterized by a cell structure mimicking the natural parenchyma of the Rattan wood used as a template for the scaffold fabrication. Both GB-1 and GB-2 scaffolds show very similar porosity extent and 3-D organization, as also revealed by mercury intrusion porosimetry. Comparing the two scaffolds, GB-1 showed slightly higher fracture strength, as well as improved stability at the stress plateau. In comparison to allograft, at the follow-up time of 6 months, both GB-1 and GB-2 scaffolds showed higher new bone formation and quality of regenerated bone (trabecular thickness, number, and separation). In addition, higher osteoid surface (OS/BS), osteoid thickness (OS.Th) osteoblast surface (Ob.S/BS), vessels/micro-vessels numbers, as well as substantial osteoclast-mediated implant resorption were observed. The highest values in OS.Th and Ob.S/BS parameters were found in GB-1 scaffold. Finally, Bone Mineralization Index of new bone within scaffolds, as determined by micro-indentation, showed a significantly higher micro-hardness for GB-1 scaffold in comparison to GB-2. These findings suggested that the biomorphic calcium phosphate scaffolds was able to promote regeneration of load-bearing segmental bone defects in a clinically relevant scenario, which still represents one of the greatest challenges in orthopedics nowadays.